ELECTRONIC PORTFOLIOS IN FOREIGN LANGUAGE LEARNING: CREATING AMOTIVATING WRITING CONTEXT IN AN EFL ELEMENTARY CLASS VIA STUDENT WEBFOLIOS - Inamlik, Ozan Sueleyman (Iated-Int Assoc Technology Education & Development, 2010)
With the emergence of 'Webfolios', language portfolios became very dynamic ones when they started to be easily seen by wider audiences. A webfolio can be defined as a medium where the best pieces of a student's work are gathered on a web page in order to exhibit his/her achievements in the cyber space. Webfolio-based writing allows students interact with their audiences via emails, chat boards, or etc. and enrich their works with visuals such as photos, pictures, videos, or etc. Thus, writing is changed into a totally more interesting, dynamic and effective process. EFL 198 course, which inspired the presence of this thesis study, is a second semester Elementary level English language course for students in the Turkish Language and Literature Department and Turkish Language Teaching Department at Eastern Mediterranean University. This thesis study was conducted to explore if converting the writing instruction in EFL 198 classes into Webfolio-based one could provide a motivating, authentic, interesting and technologically easy writing medium and context from the perspectives of 35 EFL 198 students and the researcher, who is an EFL 198 instructor, by comparing their experiences and perceptions in Webfolio design process with the ones in current writing instruction. Course instructors' perceptions on webfolio-based writing instruction, its feasibility at Turkish Medium Programs and its comparison with the recent writing instruction is used as the third data source. EFL 198 students and the researcher defined the process technologically easy, more interesting, authentic and motivating, in comparison to in-class writing instruction. Although, the EFL 198 instructors agreed on the participants' ideas, they found webfolio-based writing instruction not feasible considering the current technical and logistic conditions at EMU.
4th International Technology, Education and Development Conference (INTED) -- MAR 08-10, 2010 -- Valencia, SPAIN